Involvement of Lyt-2 and L3T4 in activation of hapten-specific Lyt-2+ L3T4+ T-cell clones. - Fazekas de St Groth, B (1986)
The murine T-cell surface molecules Lyt-2 and L3T4 play a role in the activation of antigen-specific T cells. The currently accepted model for the function of these molecules proposes that Lyt-2 and L3T4 increase the overall avidity of the interaction between the T-cell antigen receptor and antigen in association with the major histocompatibility complex (MHC) molecules on the antigen-presenting cell. We have used two unusual Lyt-2+ L3T4+ class II MHC-restricted T-cell clones to test whether Lyt-2 can substitute for L3T4 when the T-cell antigen receptor is class II MHC-restricted. Monoclonal antibodies against L3T4 profoundly inhibited antigen-induced lymphokine production by both T-cell clones. Anti-Lyt-2 monoclonal antibody had no effect. These results strongly suggest that L3T4 and the class II-restricted T-cell antigen receptors are physically close during antigen recognition, probably as part of a multimolecular complex from which Lyt-2 is excluded. The ability of L3T4 but not Lyt-2 to participate in such a complex with class II-restricted T-cell antigen receptors may explain the striking correlation between class II restriction and L3T4 expression in the peripheral T-cell pool.